EXIT (EXtrinsic Information Transfer) Chart Analysis for BCH (Bose-Chaudhuri- Hocquenghem) Codes - Melinda . (Universitas Syiah Kuala, 2010)
BCH (Bose-Chaudhuri-Hocquenghem) codes are used extensively in numerous applications in order to achieve reliable data transfer. In this paper, the parameters of BCH codes are introduced and used to investigate its applications, characteristics and performance when employed as inner and outer code in decoding method. To evaluate the parameters, three types of BCH codes: (7,4,3), (15,11,3) and (31,26,3); are applied. In addition, the implementation of BCJR (Bahl, Cocke, Jelinek and Raviv) algorithm is discussed by applying APP-SISO (a posteriori probabilities – Soft Input Soft Output) decoding for BCH codes. The proposed cheme employing inner and outer decoding of BCH codes is analyzed and compared by using EXIT characteristic of BCH decoders. The channel capacity measurements for different rates inner BCH codes are described by using BPSK modulation over AWGN channel. Lastly, the BER performances of BCH codes are observed for different types, in order to obtain better performance of BER plot indeed.